ANALISIS BANJIR DAN TINGGI MUKA AIR PADA RUAS SUNGAI CILIWUNG STA 7+646 s/d STA 15+049 - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2018)
The problem of flooding in DKI Jakarta is considered normal because almost every year can hit the city of Jakarta especially during the rainy season. In DKI Jakarta itself there are several rivers, one of which is Ciliwung River which is the most influential river in DKI Jakarta which often cause flood every year. The purpose of this research is to know the location of flood / river flood that occurs in the segments along Ciliwung River STA 7 + 646 s / d STA 15 + 049. Data processing begins with the calculation of average rainfall, frequency analysis, and then hour-time rain distribution. Method of calculation of flood discharge using the synthetic unit of Nakayasu and Gama I synthetic data. Rainfall data using 2 observation stations for 3 years rain (2014-2016). In the frequency analysis used Gumbel distribution berdasrkan test results suitability data Smirnov- Kolmogorov and Chi-Square. The result of flood peak discharge design with HSS Nakayasu on return period Q5 = 687,80 m3 / dt, Q10 = 743,21 m3 / dt, Q20 = 796,36 m3 / s, Q50 = 865,15 m3 / dt, Q100 = 916,71 m3 / s, while flood peak discharge design with HSS Gama I on return period Q5 = 347,03 m3 / s, Q10 = 372,12 m3 / s, Q20 = 396,20 m3 / s, Q50 = 427, 36 m3 / s, Q100 = 450,71 m3 / s. The design flood discharge value approaching the measured debit value is HSS Nakayasu. Steps continued using HEC-RAS 4.1.0 software to determine the capacity of river catchment by using Nakayasu discharge. After analyzing using the software, most stationing of the Ciliwung River at STA 7 + 646 to STA 15 + 049 can not accommodate the planned discharge during the 20th anniversary period, hence the need for river improvements in the form of river normalization and elevation of dikes.